Vulnerable work and strategies for inclusion: an introduction - Burgess, John; Connell, Julia (International journal of manpower, 2015)
Purpose – The purpose of this paper is to introduce this special issue volume on vulnerable work and strategies for inclusion. Definitions, measurement, analysis and policy responses to vulnerable work and strategies for inclusion are addressed before the key aspects of the nine papers included in the special issue are summarised. Design/methodology/approach – The topic of vulnerability at work is explored, before the distinguishing features of jobs that generate vulnerable conditions and the characteristics of vulnerable workers are identified. Findings – Vulnerable work is insecure and irregular with few protections accorded to the vulnerable workers who are often characterised by their age, ethnic status, gender and skill profiles. The consequences include: poor job quality, low and irregular incomes and personal/family hardship. Vulnerability is widespread across the workforce, with workers subject to work intensification, employment insecurity and poor work-life balance. Social implications – Vulnerable work and workers constitute a growing and global phenomenon. Consequently, governments and employers need to work together on programmes, such as the ILO’s decent work agenda, to ensure that basic human rights at work are widely recognised and provision to ongoing employment, safe working conditions and regular hours are offered across a variety of industries/sectors. Originality/value – This volume examines the conceptual, empirical and policy aspects of vulnerability in employment. It documents the international dimensions of vulnerability, the different forms it takes, those groups that are at risk of vulnerable employment and the underlying factors that generate and support vulnerability.